Perubahan Konsep Diri Remaja Melalui Pola Komunikasi Interpersonal Orang Tua - Khoirunnida, Rafilah; Tayo, Yanti; Yusup, Eka (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research discusses how changes in the self-concept of adolescent children can occur through changes in parental communication patterns. The theory that is used as a reference in this research is symbolic interaction theory, which in this theory will discuss how the results of the meaning obtained by teenagers from the results of the communication patterns used by their parents. The method used in this research is a qualitative method with a qualitative descriptive study approach. The results in this study reveal that through changes in communication used by parents can change the self-concept carried by children. The final conclusion obtained in this study is that both the selection of communication patterns and the level of quality of affection in the family will greatly affect changes in self-concept for adolescents